The Influence of Marketing Mix on Tourist Satisfaction in Sade Tourism Village, Central Lombok, West Nusa Tenggara - Bagas Anggara; I Nyoman Sudiarta; Ni Ketut Arismayanti (CV. AFDIFAL MAJU BERKAH, 2023)
The tourism development in Pulau Lombok has experienced rapid growth, but it still faces challenges such as a lack of human resources, substandard service quality, and inadequate supporting facilities. The objective of this study is to examine the impact of the Marketing Mix on tourist satisfaction in the Sade Tourism Village. The Marketing Mix consists of seven marketing elements, including Product, Price, Place, Promotion, People, Process, and Physical Evidence. Tourist satisfaction plays a critical role in the achievement of success within the tourism industry. The research methodology employed in this study is quantitative research, involving the distribution of questionnaires to 100 visiting tourists. Purposive Sampling was used with the criteria that respondents must be over 17 years of age. Structural equation modeling analysis using Smart PLS was employed in this research. The findings demonstrate that the dimensions of the Marketing Mix, namely Product, Price, Place, Promotion, People, Process, and Physical Evidence, have a significant influence on tourist satisfaction in the Sade Tourism Village. This study provides practical implications for service providers in the village of Sade. Service providers need to maintain aspects of the Marketing Mix, such as offering attractive tourism products, affordable pricing, effective distribution channels and promotions that can reach tourists, high-quality service processes, and an appealing appearance. By maintaining and enhancing these elements of the marketing mix, it will have an impact on tourist satisfaction.